2009
DOI: 10.1037/a0014253
|View full text |Cite
|
Sign up to set email alerts
|

Re(de)fining the orthographic neighborhood: The role of addition and deletion neighbors in lexical decision and reading.

Abstract: The influence of addition and deletion neighbors on visual word identification was investigated in four experiments. Experiments 1 and 2 used Spanish stimuli. In Experiment 1, lexical decision latencies were slower and less accurate for words and nonwords with higher-frequency deletion neighbors (e.g., jugar in juzgar), relative to control stimuli. Experiment 2 showed a similar interference effect for words and nonwords with higher-frequency addition neighbors (e.g., conejo, which has the addition neighbor con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
112
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(126 citation statements)
references
References 91 publications
(187 reference statements)
10
112
2
2
Order By: Relevance
“…That is, nonwords such as lght or ligt tend to activate their addition neighbor LIGHT at a ceiling level-which is close to the activation from the stimulus item light-and this is the reason why they activate associative/semantic information. Consistent with this view, nonwords with addition neighbors tend to produce a very high percentage of false positives in the lexical decision task (see Davis et al, 2009). What we should also indicate is that Carreiras et al (2009), who found an effect of consonant/ vowel status in a delayed letter paradigm, opted for delaying two letters-rather than one-because performance was at ceiling values when only one consonant or only one vowel was delayed in pilot work.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…That is, nonwords such as lght or ligt tend to activate their addition neighbor LIGHT at a ceiling level-which is close to the activation from the stimulus item light-and this is the reason why they activate associative/semantic information. Consistent with this view, nonwords with addition neighbors tend to produce a very high percentage of false positives in the lexical decision task (see Davis et al, 2009). What we should also indicate is that Carreiras et al (2009), who found an effect of consonant/ vowel status in a delayed letter paradigm, opted for delaying two letters-rather than one-because performance was at ceiling values when only one consonant or only one vowel was delayed in pilot work.…”
Section: Discussionmentioning
confidence: 55%
“…Bowers, Davis, and Hanley (2005) found that participants took more time to decide that seep (which has the addition neighbor sheep) was not a type of animal than to decide that it was not a type of vehicle. Furthermore, using a lexical decision task, Davis, Perea, and Acha (2009) found slower and substantially less accurate no decisions for nonwords with addition neighbors (e.g., luxry; the base word is luxury) relative to control nonwords. Davis et al also found an interference effect from higher frequency addition neighbors for word stimuli (e.g., hose because of house) in a lexical decision task and in a normal reading experiment in which the participants' eye movements were monitored.…”
Section: Experiments 1 Methodsmentioning
confidence: 94%
“…Orthographic neighborhood size affects a large number of psycholinguistic phenomena (Carreiras et al, 1997;Davis, Perea, & Acha, 2009;Grainger, 1990;Yarkoni, Balota, & Yap, 2008). For EsPal, each word was compared with all other words in the same source in order to provide an array of neighborhood properties.…”
Section: Orthographic Neighborhoodsmentioning
confidence: 99%
“…standard naming and lexical decision tasks generalize to word recognition processes while reading" (p. 392) (e.g., see Acha & Perea 2008b;Davis et al 2009;Johnson, Perea, & Rayner, 2007;Perea & Pollatsek 1998, for a few instances). Furthermore, single-word identification tasks provide ecologically valid information (e.g., when we process sign roads, the name of bus/subway stations, names of products/stores, etc).…”
mentioning
confidence: 99%